Javanese Script Reading and Writing Training with Ular Tangga Media for Elementary School-Age Children at Sanggar Pelangi Surakarta - Pribadi, Nirbito Hanggoro; Kurwidaria, Favorita; Wijayanti, Kenfitria Diah; Rahadini, Astiana Ajeng; Said, Dewi Pangestu; Veronika, Prima (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
The use of Javanese script in Javanese communication is increasingly experiencing an alarming degradation. Appropriate preservation strategies need to be implemented so that Javanese characters can be preserved and widely used again. The right effort is to carry out training in reading and writing Javanese script to the younger generation. The training activities are adapted to the cognitive level of the subject, namely learning while playing. This training was conducted at Sanggar Pelangi Surakarta with elementary school-age children as the subjects. The purpose of the training is to introduce and educate the younger generation to be able to read and write Javanese characters properly and correctly. The training was conducted with the help of ular tangga media which is recognized as accurate in optimizing the absorption of material for elementary school-age children. The training was carried out with the stages of preparation, delivery of material, playing ular tangga modified by including Javanese script elements, working on LKDP, and filling out questionnaires. The result was a significant increase in the trainees' understanding of how to read and write Javanese characters properly and correctly.